Examkrackers 101 passages in MCAT verbal reasoning - Orsay, Jonathan; Examkrackers, Inc ([Bogota, N.J.] : Osote Pub., 2002)
Eleven 85 minute full length practice MCAT verbal exams in the new MCAT format with 2,696 explanations for correct and incorrect answer choices--P. [4] of cover
Statement of responsibility from cover
Library copy donated by John Thurman, USMA 2000
Keywords: Medical colleges -- United States -- Entrance examinations -- Study guides; Medical College Admission Test -- Study guides; Reasoning -- Examinations -- Study guides; Verbal ability -- Examinations -- Study guides